(untitled) (Development Service Industry Management, 2024)
The article highlights the need for a broader perspective on ensuring the economic security of an enterprise, introducing the concept of "enterprise activity security," in which ensuring the economic security of the enterprise becomes the goal of securing as a complex process. Recently, ensuring activity security has become increasingly relevant for domestic enterprises, driven by the significant negative impact of a number of factors. For a long time in the field of economic security at the micro level, the prevailing view was that the economic security of an enterprise is mainly ensured by economic-legal and organizational measures. Attention was not paid to security measures of a different nature in ensuring economic security of the enterprise. However, the economic security of an enterprise depends on a series of events, cases, and situations that at first glance are not related to it. Ensuring the activities of the enterprise are considered from the perspective of a protective and object-subjective approach. The concept of "enterprise activity security" is disclosed using an object-subjective approach, which creates a cognitive basis for securing enterprise activities through a strongly pronounced pragmatic aspect. The imperative concepts of the object-subjective approach are "security object," "protection subject," and "protection methods," which are objectified with respect to ensuring the activities of the enterprise. Within the protective approach, it is shown that the purpose of ensuring the activities of the enterprise is to identify potential threats, prevent the realization or development of real security objects of the enterprise, and mitigate the consequences of threat realization. Explanation has been provided on the collision situation in the process of joint activities of employees performing safety and security measures. Components of enterprise activity security have been provided as a complex process, the course of which encompasses all functional types of enterprise activity and the activities of all its structural units. A list of main groups of security measures is presented based on the main vectors of enterprise activity security. Principles have been established for ensuring enterprise activity, reflecting basic guidelines and requirements, compliance with which can make this process effective.